ANALISIS BUDAYA ORGANISASI SISTIM IMBALAN DAN KOMPETENSI TERHADAP KINERJA KARYAWAN HOTEL BINTANG DUA DI KOTA BATAM - Wasiman (Postgraduate Management Journal, 2022)
This study aims to determine the effect of organizational culture, reward system and competence on employee performance in two-star hotels in Batam City. This study uses primary data through questionnaires distributed to employees of two-star hotels in Batam City. The questionnaires were distributed with a total of 123 respondents. Based on the results of the questionnaire distribution, it was found that the results of the validity test showed that all indicators and statements showed valid results, this means that the validity of all data is valid and can be continued to the reliability test stage. Normality test results. The results of the test and f test can say that organizational culture, imbalance system and competence have a significant effect on the performance of two-star hotel employees in Batam City. The result of the coefficient of determination (R2) is 0.750, meaning that this variable can be explained by the performance variable, which can be explained by the organizational culture variable, imbalance system and competence, while 25% are other variables outside the study.